2008
DOI: 10.1021/jf8011536
|View full text |Cite
|
Sign up to set email alerts
|

Sunflower Cake as a Natural Composite: Composition and Plastic Properties

Abstract: Nowadays, the end-of-life of plastic products and the decrease of fossil energy are great environmental problems. Moreover, with the increase of food and nonfood transformations of renewable resources, the quantities of agro-industrial byproducts and wastes increase hugely. These facts allow the development of plastic substitutes made from agro-resources. Many researches show the feasibility of molding biopolymers extracted from plants like a common polymeric matrix. Other natural macromolecules are used like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 36 publications
(62 reference statements)
5
19
0
Order By: Relevance
“…The chemical composition on a dry basis content of the SPC used in the extraction experiments comprised: 58 ± 4 g kg -1 moisture, 196 ± 7 g kg -1 crude protein, 256 ± 2 g kg -1 oil, 43.0 ± 0.6 g kg -1 ash, 510 ± 10 g kg -1 carbohydrates and 24 ± 2 g kg -1 CAs. These results are in accordance with Baumler et al, 3 and the chlorogenic content is close to the value reported by Geneau-Sbartai et al 35 The relative deviation ( ) of the mass balance of the extraction trials, calculated by Eqn (2), varied from 0.05% to 1.19%, indicating good precision and repeatability of the results. Figure 1 shows the sunflower seed oil yield, expressed as g oil (kg sunflower SPC) -1 (wet basis), and the CA content in sunflower oil (SFO; g kg -1 ) obtained using the process conditions under investigation.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The chemical composition on a dry basis content of the SPC used in the extraction experiments comprised: 58 ± 4 g kg -1 moisture, 196 ± 7 g kg -1 crude protein, 256 ± 2 g kg -1 oil, 43.0 ± 0.6 g kg -1 ash, 510 ± 10 g kg -1 carbohydrates and 24 ± 2 g kg -1 CAs. These results are in accordance with Baumler et al, 3 and the chlorogenic content is close to the value reported by Geneau-Sbartai et al 35 The relative deviation ( ) of the mass balance of the extraction trials, calculated by Eqn (2), varied from 0.05% to 1.19%, indicating good precision and repeatability of the results. Figure 1 shows the sunflower seed oil yield, expressed as g oil (kg sunflower SPC) -1 (wet basis), and the CA content in sunflower oil (SFO; g kg -1 ) obtained using the process conditions under investigation.…”
Section: Resultssupporting
confidence: 92%
“…The chemical composition on a dry basis content of the SPC used in the extraction experiments comprised: 58 ± 4 g kg –1 moisture, 196 ± 7 g kg –1 crude protein, 256 ± 2 g kg –1 oil, 43.0 ± 0.6 g kg –1 ash, 510 ± 10 g kg –1 carbohydrates and 24 ± 2 g kg –1 CAs. These results are in accordance with Baumler et al ., and the chlorogenic content is close to the value reported by Geneau‐Sbartai et al …”
Section: Resultssupporting
confidence: 90%
“…Of the two latter protein sources, soy proteins have been shown potential for production of base materials even stronger than those built on gluten [8,10]. The press cake of oil plants has only been evaluated for material production in a few studies, showing that the rapeseed cake and sunflower cake may be of potential interest for production of composite materials [7,17,18]. The use of press cakes or flours that also contain other substances than just proteins may thus have the potential to be used directly as composite materials instead of having to add fibres, thereby risking that the protein matrix and the fibres do not bind properly to each other [19].…”
Section: Discussionmentioning
confidence: 99%
“…The seeds contain about 20% of protein, whereas protein contents of the oil press cakes and extraction residues vary from 30% for strawy press cake to 50% for press cake obtained from dehulled seeds (Dorrell & Vick, 1997;Geneau-Sbartai, Leyris, SIlvestre & Rigal, 2008). Sunflower proteins prove to be of great interest for human nutrition, especially due to their nutritional and bio-functional properties but also because of their sensory characteristics (Sodini & Canella, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, polyphenol pre-extraction using acidic or saline media prior to alkaline protein recovery (O'Connor, 1971a;Pearce, 1984, Domínguez, Núnez & Lema, 1995 and the separation of phenolic compounds via membrane filtration after basic protein extraction under inert gas have been proposed (O'Connor, 1971b). As a consequence of major drawbacks of these solutions, Pickardt et al (2009) developed a method for mild-acidic extraction of sunflower seed proteins using sodium chloride to enhance protein solubility, both of the globulin -the major fraction of sunflower proteins -and the albumin fraction (Geneau-Sbartai et al, 2008) and to facilitate the removal of unbound phenolic compounds from the extracts, which is a prerequisite to obtain colorless protein products.…”
Section: Introductionmentioning
confidence: 99%